RCD em um sistema cimentício híbrido de uma argamassa álcali-ativada utilizada como material de reparo - Delfino, Lucas Moura (2022)
Civil construction impacts the environment in different ways and at any stage, whether at the beginning with the use of non-renewable raw materials and emission of polluting gases in the manufacture of Portland cement, or at the end with demolition, generating a high volume of waste improperly rejected. Therefore, this research sought to contribute by obtaining and strategically characterizing CDW as a precursor in alkali-activated mortars applied as a repair material. For this, a hybrid cementitious system was explored, formed by the partial replacement of 40%, 50% and 60% of metakaolin (MK) by red ceramic waste (RCW) as a supplementary precursor of Al and Si, and addition of 10%, 20 % and 30% of concrete and mortar waste (CMW) evaluated as a source of Ca. The hybrid precursors were alkaline activated by an alternative sodium silicate to the commercial one, and, together with the fine aggregate, mortars were dosed, microstructurally investigated and subjected to analysis of strength (compression and traction), workability, porosity and adhesion from the perspective of a repair material. The results showed that the inclusion of CDW as a component of a hybrid precursor in the proportions studied, preserve the properties analyzed for the most part when compared with a reference of 100% metakaolin. In general, the 60%MK/40%RCW/30%CMW ratio system presented the best performance, especially in mechanical properties, reaching 29.0 MPa in 3 days and 41 MPa in 28 days. As repair material, the analyzed traces met workability and porosity requirements, and through the failure modes, it was observed the return of the monolithic integrity of the concrete specimens in the shear adhesion in the bending and oblique shear tests, different from the direct shear that presented inconclusive results due to the applied roughness method.